Planning and control of unmanned vehicle - Ang, Melvin Jin Han (2010)
In a design report, the author will describe the process on how he planned and designed the planning and controls of the Unmanned Vehicle (UV). First, he identifies the area of scopes that he will need to cover. He split them into three different sections namely: Hardware design, Electrical Circuits design and Software programming.